Experiences with a guided trauma-focused internet- and mobile-based intervention: a qualitative study of youth’s perspectives - Christina Schulte; Cedric Sachser; Rita Rosner; David Daniel Ebert; Anna-Carlotta Zarski (European Journal of Psychotraumatology)
Introduction: Research on internet-interventions for youth with post-traumatic stress symptoms (PTSS) is limited, despite promising results in adults. A non-randomised feasibility study of a therapist-guided trauma-focused internet- and mobile-based intervention (IMI) showed potential in reducing PTSS but revealed challenges with adherence and individual fit. Insights from qualitative studies can enhance intervention quality by addressing personal needs. This study explores participants’ views on the feasibility of a therapist-guided trauma-focused IMI to improve digital trauma interventions.Methods: Semi-structured interviews based on theoretical models of acceptance and human support in IMIs were conducted with 17 of 32 participants from a self-help-based trauma-focused IMI with therapist guidance. Audio-recorded interviews were transcribed and analyzed using deductive-inductive content analysis. Independent coding resulted in good agreement (κ = .76).Results: 20 themes were identified and organised under nine dimensions: participation motivation and expectations; recruitment process; treatment adherence and everyday use of therapeutic exercises; trauma processing; non-trauma processing intervention components; technology, structure, and design of the IMI; human support; individual fit; and active factors and efficacy. The technology, structure, and design of the IMI and other non-trauma-focused components were rated positively. Trauma processing presented challenges for many but was still perceived as a helpful and relevant active factor. Some felt a lack of therapeutic support, and greater personalisation of guidance was a frequent suggestion for improving the individual fit. The IMI’s efficacy was most often perceived in its effects on improved coping with trauma and symptoms.Discussion: The study identified key themes for the feasibility of a trauma-focused IMI for youth, showing general acceptance of its design, structure, and technology. While trauma processing in IMIs poses challenges similar to face-to-face therapy, these can be addressed by clarifying the therapy rationale, making trauma processing an important active factor. Further research is needed to improve individualisation and therapeutic support intensity.Trial registration: German Clinical Trials Register identifier: DRKS00023341..